PEWARISAN NILAI TRADISI NGABUNGBANG DALAM PEMBELAJARAN SEJARAH LOKALDENGAN METODE EKSKURSI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNIVERSITAS GALUH - Wulan Sondarika; Yeni Wijayanti; Agus Budiman (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
AbstractThe specific purpose of this research is to know the historical values in Ngabungbang Tradition and to know the extent of the inheritance of historical values Ngabungbang tradition applied in learning history using excursion method.This research was conducted in History Studies Program History FKIP Galuh Ciamis University, case study in the first grade students, using qualitative descriptive research method. Data collection is done by observation, interview, and document analysis. The results showed that Ngabungbang Tradition was held every 14 months Maulud in Batulawang Village, Pataruman Sub District, Banjar City. The values of the Ngabungbang Tradition are religious, aesthetic, economical, social, disciplinary, democratic, creative, honesty, homeland and other values. Most students can understand the values contained in the Ngabungbang Tradition. Keywords: Historical Value, Ngabungbang Tradition, Local History, Excursion